From a far and lovely country - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series, 2023)
"This latest installment of the beloved No. 1 Ladies Detective Agency series finds Botswana's premier detective agency as busy as ever, with no shortage of sensitive situations requiring Mma Ramotswe's keen eye and discerning input. Through it all, Mma Ramotswe will demonstrate that there are solutions to all manner of difficulties, there to be discovered as long as one is led by kindness, grace, and logic, and can rely on the wise counsel of close friends and loved ones. Sometimes, she reminds us, the best solutions to life's problems can be found with a bit of good humor, generosity of spirit, and a steaming cup of red bush tea"--